Little busters! Refrain. Season 2 [videorecording (DVD)] ([Publisher not identified], 2015)
Riki Naoe and his teammates have finally formed a complete baseball team for the Little Busters. When they reunite, there's a strange sense of deja vu as the personal mysteries and idiosyncrasies that have permeated the game coalesce into something unexpected. As the team members fall into their roles, the pieces of the puzzle begin to fall into place. Riki learns the secrets behind his narcolepsy and a stunning truth about this world will be revealed, one that will change everything.